2013
DOI: 10.1063/1.4795164
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced phase transitions in TiH2

Abstract: Recent room temperature experiments on TiH 2 [Kalita et al., J. Appl. Phys. 108, 043511 (2010)], an important compound in hydrogen storage research, revealed a cubic (fcc, Fm-3m) to tetragonal (bct, I4/mmm) phase transition at around 0.6 GPa, which was suggested to remain stable up to at least 90 GPa. However, the simulated X-ray diffraction (XRD) pattern of the I4/mmm structure cannot explain all the diffraction peaks observed at 90 GPa. In this article, we apply the recently developed particle swarm optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…111 CSP techniques, on the other hand, predicted the following sequence of transitions: I4/mmm → P 4/nmm → P 2 1 /m at 63 and 294 GPa, respectively. 112 The computed XRD patterns of the P 4/nmm structure were found to be in better agreement with experimental results up to 90 GPa than those of I4/mmm. Figure 4: Two structures often adopted by metal hydrides: (a) the CaF 2 (fcc) structure, and (b) the I4/mmm structure.…”
Section: Group 4: Titanium Zirconium Hafniumsupporting
confidence: 61%
“…111 CSP techniques, on the other hand, predicted the following sequence of transitions: I4/mmm → P 4/nmm → P 2 1 /m at 63 and 294 GPa, respectively. 112 The computed XRD patterns of the P 4/nmm structure were found to be in better agreement with experimental results up to 90 GPa than those of I4/mmm. Figure 4: Two structures often adopted by metal hydrides: (a) the CaF 2 (fcc) structure, and (b) the I4/mmm structure.…”
Section: Group 4: Titanium Zirconium Hafniumsupporting
confidence: 61%
“…The lattice parameters and atomic positions of selected structures at favored pressures are summarized in Table SI . In comparison, we observed that in both HfH 2 and TiH 2 21 , the locations of metal and hydrogen atoms are similar for I 4/ mmm , P 4 /nmm and P 2 1 /m , respectively. In all above structures, the nearest H-H distances are 2.149 Å at 1 atm, much longer than that in the pure H 2 .…”
Section: Resultsmentioning
confidence: 75%
“…Surprisingly, we found that Cmma and P 4 /nmm are energetically nearly degenerated in the range of 0–300 GPa, and enthalpy difference is less than 1 meV/f.u.. If I 4/ mmm , P 4 /nmm and P 2 1 /m phases satisfied the stability conditions of mechanics and dynamics, the phase transition sequence of HfH 2 is similar to the TiH 2 21 . However, we found that the P 4 /nmm is not stable both in dynamical and mechanical properties (see the later discussions).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…如, Zhao等人 [46] 通过CALYPSO方法确定了实 验长期未确定的硅和锗的高压亚稳相结构; Li等人 [47] 利用CALYPSO方法确定了前人实验合成的潜在超硬 材料硼化钨化合物的结构: I4/m-4u W 2 B(-phase), I4 1 / amd-8u WB(-WB或-WB), P6 3 /mmc-4u WB 2 (-phase) 和P6 3 /mmc-4u WB 3 (WB 4 ). Gao等人 [48] 利用CALYPSO 方法确定了重要的储氢材料TiH 2 的高压相结构.…”
Section: 原理上来讲 可以通过各态历经的方法来探索势能unclassified